Short time, hard time: accounts of short-term imprisonment - Holstein, James A. (1992)
This paper presents inmates' description of their prison experience and offers alternate ways of analyzing these accounts. The study focuses on short-term male inmates in a maximum security prison. The authors discuss a variety of ways in which these inmates portray their incarcerations and note that short time inmates ironically suggest that the pains of short-term imprisonment are especially prevalent, acute, and persistent. The alternate analyses offer different perspectives on how to construe these depictions of short time as "hard time."